A note on the numerical solution for Fredholm integral equation of the second kind with Cauchy kernel. - Mahiub, Mohammad Abdulkawi; Nik Long, Nik Mohd Asri; Eshkuratov, Zainidin K. (Science Publications, 2011)
In this study, numerical solution for the Fredholm integral equation of the second kind with Cauchy singular kernel is presented. The Chebyshev polynomials of the second kind are used to approximate the unknown function. Numerical results are given to show the accuracy of the present numerical solution. The present numerical solution to the Fredholm integral equation of the second kind with Cauchy kernel is accurate.